Rancang Bangun Mesin Pencacah Cup Dan Botol Plastik - Muhammad Echan Hardinata; Nina Paramytha; Muhamad Ariandi; Timur Dali Purwanto (Universitas Darul Ulum, 2026)
The issue of PET plastic waste has driven the development of an automatic shredder machine based on Arduino with RFID security. This research employs the R&D method, utilizing key components including the HC-SR04 ultrasonic sensor, DC motor, and RFID RC522 module. Test results demonstrate optimal performance with 96% sensor accuracy and a security system that only responds to registered cards. This device is effective for small-scale recycling, equipped with LED indicators and a buzzer alarm. Its main advantages are process automation and increased community participation in recycling. Future development can focus on capacity improvement by replacing blades with a crusher and IoT integration. This innovation offers a practical solution for plastic waste management while supporting the circular economy.